Endoscopic treatment of intracranial arachnoid cysts: A retrospective analysis of a 25-year experience - Oertel, Joachim; Linsler, Stefan; Wagner, Wolfgang; Gaab, Michael; Schroeder, Henry; Rediker, Jana (Operative Neurosurgery, 2021)
BACKGROUND: Since the development of neuroendoscopy, pure endoscopic fenestration for intracranial arachnoid cysts (ACs) became more and more popular and is actually preferred by many neurosurgeons. OBJECTIVE: To explore their techniques and experiences with endoscopic treatment of intracranial ACs over a 25-yr period. METHODS: A total of 95 endoscopic procedures in 87 patients with 88 intracranial ACs performed at the authors’ departments between February 1993 and October 2018 were retrospectively analyzed. Particular respect was given to surgical technique, complications, patients’ outcome, and radiological benefit in relation to cyst location. RESULTS: Patients’ ages ranged from 23 d to 81 yr (mean: 29.9 yr). Cysts were located temporobasal (n = 31; 35.2%), paraxial supratentorial (n = 14; 15.9%), suprasellar/prepontine (n = 14; 15.9%), quadrigeminal (n = 12; 13.6%), infratentorial (n = 11; 12.5%), and supratentorial intraventricular (n = 6; 6.8%). Four different endoscopic techniques were applied: cystocisternostomies (n = 48; 50.5%), ventriculocystostomies (n = 23; 24.2%), cystoventriculostomies (n = 14; 14.7%), and ventriculocystocisternostomies (n = 10; 10.5%). Pure endoscopic technique was feasible in 89 of the 95 surgeries (93.7%). Clinical improvement was documented after 82 surgeries (86.3%) and radiological benefit after 62 surgeries (65.3%). Recurrences developed in 8 cases (8.4%). Overall complication rate was 21.1% (n = 20), postoperative new shunt dependency was observed in 4.2% of the cases (n = 4). CONCLUSION: Pure endoscopic AC fenestration is a safe, effective, and less invasive technique providing high success and low permanent complication rates. The most frequent temporobasal cysts are the most difficult to treat endoscopically. A long-term follow-up is recommended because recurrences may occur many years after first treatment.
CRIS-Team Scopus Importer:2023-12-20
Keywords: Arachnoid cysts; Cystocisternostomy; Cystoventriculostomy; Neuroendoscopy; Ventriculocystocisternostomy; Ventriculocystostomy